2021
DOI: 10.1016/j.techfore.2021.120732
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the global economic impact of the coronavirus outbreak: Evidence from the main cluster countries

Abstract: This study measures the global economic impact of the coronavirus outbreak. This pandemic is characterized by demand and supply shocks, leading to restrictions on trade, product and service transactions, and capital flow mobility. We investigate its impact on currency markets, stock market performance, and investor fear sentiment. We employ an empirical, time-scale approach based on the continuous wavelet transform—appropriate for time-series characteristics during times of turmoil. Based on daily data for fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…Olakojo et al (2021) showed that negative asymmetry (length of doom > boom) in the stock market will last longer in low-income countries (often emerging countries) than in high- and middle-income countries (usually developed countries). Third, tests in main cluster countries revealed that the stock market was more sensitive to deaths than infected cases of COVID-19 (Apergis and Apergis et al , 2020; Louhichi et al , 2021; Zoungrana et al , 2021). However, the number of cases still has a serious impact on developing countries (Hashmi et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Olakojo et al (2021) showed that negative asymmetry (length of doom > boom) in the stock market will last longer in low-income countries (often emerging countries) than in high- and middle-income countries (usually developed countries). Third, tests in main cluster countries revealed that the stock market was more sensitive to deaths than infected cases of COVID-19 (Apergis and Apergis et al , 2020; Louhichi et al , 2021; Zoungrana et al , 2021). However, the number of cases still has a serious impact on developing countries (Hashmi et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Previous studies found a negative relationship between the COVID-19 fear index and their stock returns. Shear et al (2020) found that enhanced investors’ attention to the pandemic resulted in declining stock market returns, while Ding et al (2020), Deb (2021); and Louhichi et al (2021) found that market sentiment toward the pandemic had significant effects on stock price volatility. Lockdown policies are taken by the governments facing COVID-19 enhanced investor positive sentiment toward stock market returns (Chundakkadan, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This global crisis that has been described as "humanity's worst crisis since World War II" by the UN Secretary-General Antonio Guterres (France24 2020), strongly impacted different aspects of the global economy (Donthu and Gustafsson 2020;Louhichi et al 2021;Mulugeta et al 2021;Padhan and Prabheesh 2021;Wunder et al 2021;Vieira et al 2021), by nearly 2.7 trillion US dollars as estimated by Bloomberg (Bloomberg 2020). Based on the OECD Interim Economic Outlook (March 2020), the pandemic is a crucial threat to the economic growth of all countries in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In the likely case of new outbreaks of old and new transmissible diseases, this resilience-enhancing strategy would reduce the need for extraordinary measures such as lockdowns and restrictions on personal mobility and social interactions. While these measures were necessary to bring the contagion rates under control and avoid further economic disruption ( Aum, Lee, Shin, 2021 , Kochańczyk, Lipniacki, 2021 ), they have high social and economic costs ( Gharehgozli, Nayebvali, Gharehgozli, Zamanian, 2020 , Louhichi, Ftiti, Ameur, 2021 , Mahmud, Riley, 2021 , Mandel, Veetil, 2020 , Martin, Markhvida, Hallegatte, Walsh, 2020 , Tisdell, 2020 ).…”
Section: Introductionmentioning
confidence: 99%